Study of camel urine metabolic composition by NMR spectroscopy and mass spectrometry - Koroma, Kalie (2023)
Camel urine has been used in folk medicine since ancient times due to its alleged therapeutic benefits against several illnesses. Some in vitro and in vivo studies have demonstrated camel urine to have a range of biological activities, including gastric and liver protective effects, as well as antiviral and anticancer actions. However, the urine components that cause these effects are still largely unknown. In this work, we have employed Nuclear Magnetic Resonance (NMR) and Liquid Chromatography coupled to Mass Spectrometry (LC-MS) to analyse camel urine, aiming to advance current knowledge on the small molecules (metabolites) present in this complex biofluid. These metabolomic approaches have enabled the identification of about 90 compounds, from different chemical families, including carboxylic acids, phenolic compounds, amino acids and derivatives, carbohydrates, polyalcohols, amines and nucleosides. This represents an important step towards a better understanding of the metabolic composition of camel urine and its potential exploitation as a source of bioactive compounds.